2011
DOI: 10.1111/j.1750-8606.2011.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Directions in Human-Animal Interaction Research: Child Development, Health, and Therapeutic Interventions

Abstract: Research on human-animal interaction (HAI) is a relatively new field of inquiry for developmental scientists seeking to understand the potential role pets play in children's health and well-being. It has been documented that pets offer a source of emotional support to children. However, most studies focusing on how animals affect children's health are limited and stop short of providing answers to key developmental questions. Addressing this need, beginning in 2008, scientists at the Eunice Kennedy Shriver Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 28 publications
1
67
0
10
Order By: Relevance
“…A 1987 conference, The Health Benefits of Pets, held by the National Institutes of Health (NIH), included a call for research on the influence of pets in child development and their potential social and therapeutic effects. Nonetheless, a workshop held two decades later still noted the need for such research; that workshop, sponsored by a public-private partnership established in 2008 between the NIH's Eunice Kennedy Shriver National Institute of Child Health and 3 Human Development (NICHD) and the WALTHAM Centre for Pet Nutrition, a division of Mars, Inc., also led to the formation of a research program at the NICHD (Esposito, McCune, Griffin, & Maholmes, 2011). Since then, there have been three research solicitations and the NIH has funded 21 grants on HAI, including several that are relevant to the inclusion of animals in education settings.…”
Section: Research On Haimentioning
confidence: 99%
“…A 1987 conference, The Health Benefits of Pets, held by the National Institutes of Health (NIH), included a call for research on the influence of pets in child development and their potential social and therapeutic effects. Nonetheless, a workshop held two decades later still noted the need for such research; that workshop, sponsored by a public-private partnership established in 2008 between the NIH's Eunice Kennedy Shriver National Institute of Child Health and 3 Human Development (NICHD) and the WALTHAM Centre for Pet Nutrition, a division of Mars, Inc., also led to the formation of a research program at the NICHD (Esposito, McCune, Griffin, & Maholmes, 2011). Since then, there have been three research solicitations and the NIH has funded 21 grants on HAI, including several that are relevant to the inclusion of animals in education settings.…”
Section: Research On Haimentioning
confidence: 99%
“…Given these social impairments in children with ADHD, animal-assisted interventions can contribute to addressing these difficulties, as it has been demonstrated that animals act as social catalysts and have socializing effects (Wilson & Netting, 1983;Gunter, 1999;Kruger & Serpell, 2010;Esposito, McCune, Griffin, & Maholmes, 2011;O'Haire, 2013). Dogs in particular promote opportunities for social interaction and facilitate social learning, which enhances socio-emotional development and often results in improved social functioning (Melson, 2001).…”
Section: Socializing Effectsmentioning
confidence: 99%
“…The aims of this workshop were to provide the scientific community with a synthesis of current knowledge, to outline a framework for future research, and to supply the public with the information needed to make informed decisions regarding the health benefits of pets. More recently, the NIH -Mars-WALTHAM public-private partnership, established in 2008 (Esposito, McCune, Griffin, & Maholmes, 2011), led to a series of workshops and associated Requests For Applications (RFAs) for grant funding from the NIH (McCune et al, 2014). The most recent workshop from the partnership focused on animal-assisted interventions in special populations, and is the basis for a special series of five papers which we now introduce.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the efficacy of AAI as a practice remains in its infancy (Griffin, McCune, Maholmes, & Hurley, 2011;McCune et al, 2015). In particular, most AAI research is conducted in the absence of a "developmental lens" that would take into account the individual's developmental history and status, including age at first exposure to, periodicity, and nature of their human-animal interaction (HAI) experiences, and how these might moderate the efficacy of the AAI (Esposito, McCune, Griffin, & Maholmes, 2011;Jalongo, 2015;Melson, 2003).…”
Section: Introductionmentioning
confidence: 99%